(yearly worked solutions) pure physics O level exam papers (Gce O Level 2001-2011) - Ahmed, masood (Redspot pub; Pakistan, 2011)
"Pure Physics (Yearly Worked Solutions)" is a practical resource offering step-by-step solutions to past physics exam papers, helping students enhance their problem-solving skills and improve their understanding of key concepts in preparation for exams.